Climate‐driven divergent long‐term trends of forest beetles in Japan. (29th July 2022) - Evans, Maldwyn J.; Barton, Philip; Niwa, Shigeru; Soga, Masashi; Seibold, Sebastian; Tsuchiya, Kazuaki; Hisano, Masumi
Abstract: Concerning declines in insect populations have been reported from Europe and the United States, yet there are gaps in our knowledge of the drivers of insect trends and their distribution across the world. We report on our analysis of a spatially extensive, 14‐year study of ground‐dwelling beetles in four natural forest biomes spanning Japan's entire latitudinal range (3000 km). Beetle species richness, abundance and biomass declined in evergreen coniferous forests but increased in broadleaf‐coniferous mixed forests. Further, beetles in evergreen coniferous forests responded negatively to increased temperature and precipitation anomalies, which have both risen over the study's timespan. These significant changes parallel reports of climate‐driven changes in forest tree species, providing further evidence that climate change is altering forest ecosystems fundamentally. Given the enormous biodiversity and ecosystem services that forests support globally, the implications for biodiversity change resulting from climate change could be profound. Abstract : With recent concerns about catastrophic insect declines in the US and Europe, research that provides evidence for insect trends in other regions and in forest ecosystems is crucial. We report on data of forest beetles collected over a 14‐year period in forest plots across the whole latitudinal range of Japan (3000 km). Using these data, we show declines in evergreen coniferous forests accompanied with community changes in other forest biomes.